Bioengineering Novel Floating Nanoparticles for Protein and Drug Delivery. (2016) - DasSarma, Priya; Karan, Ram; Kim, Jong-Myoung; Pecher, Wolf; DasSarma, Shiladitya
Abstract: Gas vesicle nanoparticles (GVNPs) are hollow protein nanoparticles produced by Halobacterium sp. NRC-1 which are beingengineered for protein delivery. To advance thebioengineering potential of GVNPs, a strain of NRC-1 deleted for the gvp C gene (Δ gvp C) was constructed and a synthetic gene coding for Gaussia princeps luciferase wasfused to an abbreviated gvp C gene on an expression plasmid. When introduced into theΔgvpC strain, an active GvpC-luciferase fusion protein bound to GVNPs resulted. These results represent both a technical improvement in the GVNP display system and its expansionforthe display of active enzymes.